Collaborative Learning Environment for English Language Learning - Pandey, Shiv Ram; Kaudal, Durga Nidhi (A Bi-annual South Asian Journal of Research & Innovation, 2024)
This research article is on ‘Collaborative Learning Environment for English Language Learning in Private Schools in Kathmandu: A Case of Grade Five’. The study explores how private school teachers create collaborative learning environment for the English language learners. The study explores how and why the collaborative learning environment has been created to teach the English language learners in and out of the classroom. The study adopted qualitative research method and case study design to collect and analyze data from a single participant. In-depth interview and observation techniques were used to collect rich data. The participant was selected purposively. It is expected that the research outcome provides a significant ground for rethinking, reforming, planning, designing and implementing educational strategies in Nepal.